EFFECTS OF DIFFERENT CALCIUM-SILICATE BASED MATERIALS ON FRACTURE RESISTANCE OF IMMATURE PERMANENT TEETH WITH REPLACEMENT ROOT RESORPTION AND OSTEOCLASTOGENESIS - HABIB , S; ASLAM , S; FATIMA , U; REHMAN , MU; MOHSIN , KA; AHMED , Z (Biological and Clinical Sciences Research Journal, 2024)
Immature permanent teeth with replacement root resorption pose challenges in dental treatment due to compromised structural integrity. Calcium-silicate based materials show promise in promoting dentin genesis and tissue repair, but their effects on fracture resistance in such teeth remain unclear . Objective: This study aimed to investigate the impact of different calcium-silicate based materials on fracture resistance and osteoclast genesis in immature permanent teeth with replacement root resorption. Methods: A prospective experimental study was conducted on 60 patients at Lahore medical and dental college, Lahore from September 2023 to March 2024. Patients were divided into three groups receiving Bio dentine, White MTA, or Bio-C Repair as part of their endodontic treatment. Fracture resistance was assessed using mechanical testing, while osteoclast genesis was evaluated histologically. Patient-reported outcomes and radiographic findings were also recorded. Results: Bio dentine exhibited the highest fracture resistance and lowest osteoclast activity, followed by White MTA and Bio-C Repair. Patients treated with Bio dentine reported lower postoperative pain levels and higher treatment satisfaction. Radiographic evaluation showed favorable periapical healing and dentin formation in all groups. Conclusion: The study concludes that Bio dentine may offer superior fracture resistance and biocompatibility compared to White MTA and Bio-C Repair in immature permanent teeth with replacement root resorption. These findings support Bio dentine’s potential as an effective therapeutic agent for enhancing the durability and functionality of compromised dental structures. Further research is needed to validate these results and optimize treatment strategies for managing such clinical scenarios.